Utility of Fine Needle Aspiration Cytology in the Evaluation of Lymphadenopathy - Hashmi, Atif A (Cureus, 2020)
Introduction Fine needle aspiration cytology (FNAC) is a quick, effective and relatively inexpensive technique to evaluate the visibly accessible superficial masses. As cervical, axillary and inguinal lymphadenopathies are commonly encountered clinical problems, in this study, we evaluated the utility of FNAC for assessment of lymphadenopathy. Methods A retrospective observational study was conducted in the Department of Cytopathology, Liaquat National Hospital and Medical College, over the duration of three years. A total of 559 cases were included in the study that underwent FNAC. After palpation, two to three passes were performed with a 22-23 gauge needle along with a plunger for FNAC. The obtained material was spread on three slides that were then stained with hematoxylin and eosin (H & E), Papanicolaou (PAP), and Diff-Quik methods. The remaining material was used for cell block preparation. Results The mean age of the patients was 37.05±18.03 years. In 98.7% of cases, the material was adequate for a satisfactory cytological examination. The most common site of FNAC was the cervical lymph node and tuberculous lymphadenitis (37%) was the most common diagnosis on FNAC, followed by reactive lymphadenitis (27.2%). Reactive lymphadenitis was seen more frequently in the younger age group (<15 years), whereas metastatic carcinoma was more commonly seen in the older age group (>50 years). Tuberculous lymphadenitis was noted more frequently in the middle age group (16-35 years). Moreover, tuberculous lymphadenitis was noted more commonly in cervical lymph nodes, while metastatic carcinoma was more frequently observed in axillary and inguinal lymph node FNACs. Conclusion FNAC is a quick and reliable method to categorize the cause of lymphadenopathy into reactive, inflammatory/infectious, metastatic, and lymphoproliferative, avoiding the necessity of an incisional/trucut biopsy. Moreover, age, gender, and site of involvement are useful predictors of the cause of lymphadenopathy. We noted that in the younger age group, reactive lymphadenitis was more common, whereas tuberculous lymphadenitis and metastatic carcinoma were more frequent in middle and older age groups, respectively. On a similar note, tuberculous lymphadenitis was more frequent in cervical lymph nodes than axillary and inguinal lymph nodes, while metastatic carcinoma was more common in these latter two sites.